Metal- and Additive-Free Intermolecular Aziridination of Olefins Using N-Boc-O-tosylhydroxylamine - Jat, Jawahar L.; Chandra, Dinesh; Kumar, Puneet; Singh, Vikram; Tiwari, Bhoopendra (Synthesis, 2022)
A metal and additive-free stereospecific direct N-H and N-Me aziridination of inactivated olefins is disclosed using N-Boc-O-tosylhydroxylamine (TsONHBoc) as an aminating agent in hexafluoroisopropanol (HFIP). The use of TsONHBoc, which generates the free aminating agent in situ under the reaction conditions, has several inherent advantages over other similar agents, such as low cost, easy access, and stability (non-explosiveness) during storage over a longer time.
Keywords: aziridination; TsONHBoc; metal and additives free; stereospecific; regioselective